Thrifting Import in the Perspective of Qur'anic Muamalah Exegesis, Social Fiqh, and Environmental Ethics within the SDGs Framework - Mutaqin, Enjen Zaenal; Ridwan, R; Naqiyah, N; Ahmed, Ishfaq (QiST: Journal of Quran and Tafseer Studies, 2025)
This study investigates the legality, socio-environmental implications, and policy relevance of imported second-hand clothing (thrifting import) using an integrative theoretical framework that explicitly combines ecotheology, fiqh sosial Kiai Sahal Mahfudh, and fiqh muamalah. The research addresses the central problem of how thrifting imports intersect with Islamic legal norms, sustainability ethics, and state regulations amidst rising concerns over waste, illegal trade, and threats to local industries. Using qualitative library research supported by hermeneutic and content analysis methods, this study examines classical and contemporary fiqh sources, Qur'anic exegesis on muamalah, literature on circular economy and sustainable consumption, as well as regulatory documents and statistical reports. The findings show that thrifting import does not fulfill key requirements of a valid sale (ma‘qūd ‘alayh), contains elements of gharar and bāṭil, contributes to ecosystem degradation, and disrupts the textile industry. The study also formulates policy implications by proposing a maqāṣid-oriented regulatory design, including empowerment strategies for affected small traders, strengthening domestic industry, and environmental sustainability measures. These recommendations highlight the importance of integrating Islamic legal ethics with national economic and ecological policies.